Criticality and correlated dynamics at the irreversibility transition in periodically driven colloidal suspensions. (22nd March 2016) - Tjhung, Elsen; Berthier, Ludovic
Abstract: One possible framework to interpret the irreversibility transition observed in periodically driven colloidal suspensions is that of a non-equilibrium phase transition towards an absorbing reversible state at low amplitude of the driving force. We consider a simple numerical model for driven suspensions which allows us to characterize in great detail a large body of physical observables that can be experimentally determined to assess the existence and universality class of such a non-equilibrium phase transition. Characterizing the behaviour of static and dynamic correlation functions both in real and Fourier space we determine in particular several critical exponents for our model, which take values that are in good agreement with the universality class of directed percolation. We also provide a detailed analysis of single-particle and collective dynamics of the system near the phase transition, which appear intermittent and spatially correlated over diverging timescales and lengthscales, and provide clear signatures of the underlying criticality.